A candidate regulatory variant at the TREM gene cluster associates with decreased Alzheimer's disease risk and increased TREML1 and TREM2 brain gene expression - Carrasquillo, Minerva; Allen, Mariet; Burgess, Jeremy D.; Medway, Christopher; Morgan, Kevin (Elsevier, 2017)
Introduction: We hypothesized that common Alzheimer's disease (AD)-associated variants within the triggering receptor expressed on myeloid (TREM) gene cluster influence disease through gene expression.